2013
DOI: 10.1159/000349984
|View full text |Cite
|
Sign up to set email alerts
|

RimabotulinumtoxinB versus OnabotulinumtoxinA in the Treatment of Masseter Hypertrophy: A 24-Week Double-Blind Randomized Split-Face Study

Abstract: Background: Masseter hypertrophy can be ameliorated by botulinum toxin. Objective: To compare the efficacy and safety of RimabotulinumtoxinB (BTX-B) and OnabotulinumtoxinA (BTX-A) in the treatment of masseter hypertrophy. Methods: Sixteen women with bilateral masseter hypertrophy received single injections of BTX-A or BTX-B at a dose ratio of 1:50 or 1:70 in a 24-week double-blind randomized split-face study. Results: Both BTX-A and BTX-B produced significant improvements in masseter hypertrophy. The maximum v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In addition, one study compared Ona‐A and Abo‐A, while another split face study compared Ona‐A and Inco‐A. Of studies using BoNT‐B, 1 split face study from 2013 compared the effects between Rima‐B and Ona‐A—the 2 serotypes were found to be of similar efficacy, but Ona‐A produced a longer‐lasting result. In addition, there were 5 articles that did not indicate the serotype or subtype of BoNT used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one study compared Ona‐A and Abo‐A, while another split face study compared Ona‐A and Inco‐A. Of studies using BoNT‐B, 1 split face study from 2013 compared the effects between Rima‐B and Ona‐A—the 2 serotypes were found to be of similar efficacy, but Ona‐A produced a longer‐lasting result. In addition, there were 5 articles that did not indicate the serotype or subtype of BoNT used.…”
Section: Resultsmentioning
confidence: 99%
“…BoNT-A can be further separated into multiple subtypes based on individual commercial formulations such as molecular weight or presence of complexing proteins. 31 -the 2 serotypes were found to be of similar efficacy, but Ona-A produced a longer-lasting result. In addition, there were 5 articles that did not indicate the serotype or subtype of BoNT used.…”
Section: Types Of Toxinmentioning
confidence: 87%
“…After manuscript review, two were excluded for being duplicates and 27 were excluded for not being RCTs. This left 181 articles in 27 journals to be included in the review . Of these, 137 studies had parallel‐armed control groups, 42 had placebo control groups, one was a cross‐over design and one used no treatment as the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Full-face transition in a 25-year-old male-to-female transgender patient (Figure 3). This patient, who had been on estrogen therapy for over 2 years, received 4 units of onabotulinumtoxinA at each lateral end of her eyebrows Inject into forehead, glabellar, or periorbital areas to eliminate dynamic rhytids and create a more feminine forehead, angled eyebrow shape, and widened eyes; 5,9 injection into the superolateral orbital portion of the orbicularis oculi muscle may raise the lateral brow, 44,45 whereas injection into the palpebral portion of the orbicularis oculi may widen the eye aperture, with injections placed inferior to the lower eyelid and lateral to the midpupillary line 43 Inject along zygomatic arch to help cheeks appear more prominent and contoured; inject into anterior malar area to create a prominent, full, and more feminine apex peaking more superiorly and laterally 5,9 Atrophy the glabellar musculature to help create a more obtuse nasofrontal angle; 5 weaken the depressor septi nasi muscle to feminize the nose by lifting the nasal tip; weaken the nasal alar muscles to decrease alar flare Inject medially into chin to give it a more-rounded, less-square contour Inject into the masseter and mentalis muscles to cause gradual atrophy, decreasing the prominence of the male jawline and making the face appear more heart shaped 44,46 Inject into lips to augment them 9 and into the perioral region to improve lip contour and decrease rhytids 47 Address signs of aging such as temple volume loss, marionette hollowing, prejowl sulcus, and tear trough development…”
Section: Case Study #2 (Contributed By Vw)mentioning
confidence: 99%